Effects of Red Coconut Tembuluk (Cocos nucifera var. rubescens) Extract on Uric Acid Level Reduction in Mice (Mus musculus) - Sukmawati Sukmawati; Sutrisnawati Sutrisnawati; Manap Trianto; Masrianih Masrianih; Fatmah Dhafir; I Nengah Kundera (Biology, Medicine, & Natural Product Chemistry, 2026)
Increased levels of uric acid in the blood can lead to metabolic disorders such as gouty arthritis, which require effective management. This study aimed to determine the effect of red coconut tembuluk extract (Cocos nucifera var. rubescens) on reducing uric acid levels in mice (Mus musculus). The study employed an experimental research design using a Completely Randomized Design (CRD). A total of 28 mice were used, divided into seven groups with four replications each. The groups consisted of a normal control group (KN), which received food and water ad libitum; a negative control group (K+); a positive control group (K-); and four treatment groups (PI, PII, PIII, and PIV). The negative control group (K+), positive control group (K-), and all treatment groups were induced with lard oil for 14 days to increase uric acid levels. The positive control group (K?) was treated with allopurinol at a dose of 0.026 mg per 20 g body weight. The normal control (KN) and negative control (K+) groups received food and water ad libitum without extract administration. Treatment group PI received 10% red coconut tembuluk extract, PII received 20%, PIII received 40%, and PIV received 80%. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that administration of red coconut tembuluk extract significantly reduced uric acid levels in mice induced with lard oil. The most effective concentration in reducing uric acid levels was 80% (PIV), with an average uric acid level of 5.4 mg/dL.